2022
DOI: 10.3389/fped.2021.773484
|View full text |Cite
|
Sign up to set email alerts
|

Does Orthokeratology Wearing Affect the Tear Quality of Children?

Abstract: Orthokeratology is currently known as one of the most effective methods of myopia control in the process of rapid deterioration of the global myopia prevalence. As orthokeratology is widely used, it is necessary to evaluate its complications reasonably and accurately. Eye surface problems in children, such as dry eyes, have received increasing attention. At present, there is no conclusive evidence on how orthokeratology affects the ocular surface, especially the tears. To our knowledge, this is the first study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Myopia is the result of genetic and environmental factors, and its pathogenesis and progression mechanism are still unclear. At present, the mainstream mechanisms include regulation mechanism, hyperopic defocusing mechanism, etc [ 41 , 42 ]. The stimulating effect of periretinal hyperopia defocus on central axial myopia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myopia is the result of genetic and environmental factors, and its pathogenesis and progression mechanism are still unclear. At present, the mainstream mechanisms include regulation mechanism, hyperopic defocusing mechanism, etc [ 41 , 42 ]. The stimulating effect of periretinal hyperopia defocus on central axial myopia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the poor coordination with the examination of children, we used non-invasive Keratograph 5M ( 45 ) and LipiView ( 46 ) in this study to obtain objective parameters. Besides, we balanced the effect of time spent outdoors, electronic screen use, and parental smoking that might affect tear quality ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, contact lens wearing is believed to be one of the main causes of dry eye ( 13 ). Ocular surface problems of dry eyes in children wearing OrthoK have raised increasing attention from physicians ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…[43] Our team conducted a meta-analysis related to the use of OK lenses before October 19, 2020, and found that they can affect the stability of the tear film but have no significant effect on tear secretion. [44] A number of factors can influence the results of this study, such as the measurement method used to measure the breakup time of the tear film, the preparation for wearing OK lenses, night sleep time, and the duration of measures. Therefore, studies on the effect of orthokeratography on ocular surface homeostasis require stricter control of these variables.…”
Section: Effect Of Ametropia and Its Treatment Measures On Ocular Sur...mentioning
confidence: 99%